Construção de um forno tubular elétrico alternativo e de baixo custo - RAIOL, Wesley Richeley da Cunha (2022)
This course conclusion work consists in the construction of an electric tubular furnace with low financial cost. The kiln's main characteristics are its cost/benefit and its working temperature, which can reach within a safety margin of 1000ºC, being operated in temperature ramps, according to the needs of the work carried out. Another great difference in the construction of this furnace, in addition to the cost/benefit, its design allows it to be operated in vertical and horizontal positions. With a similar operating activity, but with a cost/benefit far below industrial and traditionally marketed furnaces, the tubular furnace presents itself as an alternative for heat treatments in metal analysis, sample calcination, oxide production and in countless jobs where it is necessary gradual use of temperature. For the construction of the CONTEMP CTM 45 controller oven, switching, power supply cables, temperature sensor (type K thermocouple), solid state relay (SSR), heating resistance (Nicrome V) and electro-electronic components required for construction were used this work. In order to reduce the thermal heating in the vicinity of the machine, thermal insulation was applied to the resistance cylinder (work chamber). In addition, characteristics of the equipment and power circuits were described. Finally, the conclusion was presented, which highlights the work as an alternative of low financial cost compared to industrialized ovens of the same size.